Relationship between Knowledge, Attitude, and Practice of Mothers Maintaining Children’s Dental Health with Status Early Childhood Dental Caries 5 Years Old in Pondok Labu Village, South Jakarta - Siti Nurbayani; Pudentiana Reno Enggarwati (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This study aims to determine the relationship between mothers’ knowledge, attitudes, and practice in maintaining children’s dental health with caries status of milk teeth in Early Childhood students aged five years in Pondok Labu Village, Cilandak, South Jakarta. Data analysis was carried out using a computer program including univariate and bivariate (chi-square) analysis. The results showed that most students ( 68.5%) had caries in their milk teeth, and only 31.5% were caries-free. These results indicate that the caries-free state of students aged five years in the Early Childhood Pondok Labu sub-district, South Jakarta is still far from the target set by WHO as well. Indonesia’s national target is healthy, where the caries-free rate in children aged five years is targeted at 90%. However, this result is better than the study on the prevalence of dental caries in children 3-5 years old in Sawah Village, Ciputat Subdistrict, and Cilandak Village, Pasar Minggu Subdistrict in 2003, where the results obtained that the prevalence of caries in milk teeth was 86.4% or a caries-free rate of 13.6. % in children aged five years. The results also showed that mothers’ knowledge, attitudes, and practices in maintaining their children’s dental health were good, where 83.9 % of mothers had good knowledge, 54% of mothers had good attitudes, and 69.4% of mothers had good practices and good in maintaining the dental health of their children. Still, statistical tests showed no significant relationship between the variables of mothers’ knowledge, attitudes, and practices in keeping children’s dental health with the presence or absence of caries in the baby’s milk teeth.